Pembangunan Portal untuk Perniagaan Komputer bagi IKS di Negeri Kedah Darul Aman - Nadia, Abdul Wahab (2003)
Nowadays, we can see that industrial portal has been widely used. One of the factor that contributes to the increasing number of industrial portal is its capability to offer various functions for the organizations so that they will be able to arrange and organized the collection of information and services from different sources to be distributed to numerous of users. This research aims to come out with a vertical portal for computer industry in SME in the state of Kedah Darul Aman. This research is also meant to discuss about the objectives, scopes, and literature review regarding to this portal. The methodology used, development and implementation and the contribution of this system will also be discussed in this research.